Classification and Grading of Low‐Grade Astrocytic Tumors in Children - Giannini, Caterina (Brain Pathol, 2008)
This article reviews current perspectives in the classification and grading of astrocytomas in children and calls attention to several histologically distinct groups of low‐grade tumors that characteristically arise during childhood. Recognition of these tumors and the range of histological features that they may exhibit is essential for making rational assessments regarding their expected behavior and, more importantly, for guiding therapeutic intervention. For example, pleomorphic xanthoastrocytoma, which may exhibit “anaplastic” features, generally carries a relatively favorable prognosis and should not be classified with other high‐grade gliomas, such as anaplastic astrocytoma and glioblastoma multiforme. Similarly, the finding of anaplastic features, such as vascular proliferation or necrosis, in pilocytic astrocytomas does not automatically portend the unfavorable prognosis that such features would imply for “diffuse” astrocytomas. Increased appreciation of the morphological diversity of astrocytomas in children should help to improve the management of children with low‐grade astrocytic tumors by avoiding potentially dangerous overtreatment of otherwise indolent lesions.